Cohort effects and the returns to education in West Germany - Bernhard Boockmann; Viktor Steiner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
Using a Mincer-type wage function, we estimate cohort effects in the returns to education for West German workers born between 1925 and 1974. The main problem to be tackled in the specification is to separately identify cohort, experience, and possibly also age effects in the returns. For women, we find a large and robust decline in schooling premia: in the private sector, the returns to a further year of post-compulsory education fell from twelve per cent for the 1945-49 cohort to about seven per cent for those born in the early 1970s. Cohort effects in men?s returns to education are less obvious, but we do find evidence that they, too, have declined. We conclude by identifying possible reasons for the decline.
Keywords: J31; 330; returns to education; cohort effects; population ageing; Bildungsertrag; Schätzung; Kohortenanalyse; Geschlecht; Alternde Bevölkerung; Deutschland